2022
DOI: 10.1111/jce.15387
|View full text |Cite
|
Sign up to set email alerts
|

Single ring isolation for atrial fibrillation ablation: Impact of the learning curve

Abstract: Introduction: Although single ring isolation is an accepted strategy for undertaking pulmonary vein (PV) and posterior wall isolation (PWI) during atrial fibrillation (AF) ablation, the learning curve associated with this technique as well as procedural and clinical success rates have not been widely reported.Methods and Results: Prospectively collected data from 250 consecutive patients undergoing de novo AF ablation using single ring isolation. PWI was achieved in 212 patients (84.8%) and PV isolation withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, if the PVs would have been reconnected, a more distal reisolation of the PVs or a single ring isolation with inferior line sparing could have been a bail-out option. 10 , 11 We identified a gap in the roof line and the posterior wall could be reisolated by RF ablation anterior to the initial roof line to avoid ablation on the posterior wall. The clinical arrhythmias in this patient were a left-sided focal AT and a macroreentrant AT around the mitral valve.…”
Section: Discussionmentioning
confidence: 95%
“…However, if the PVs would have been reconnected, a more distal reisolation of the PVs or a single ring isolation with inferior line sparing could have been a bail-out option. 10 , 11 We identified a gap in the roof line and the posterior wall could be reisolated by RF ablation anterior to the initial roof line to avoid ablation on the posterior wall. The clinical arrhythmias in this patient were a left-sided focal AT and a macroreentrant AT around the mitral valve.…”
Section: Discussionmentioning
confidence: 95%
“…Some previous studies reported the ablation technique of SRI for paroxysmal and persistent AF ( 6 , 16 ) and that SRI could improve the success rate ( 7 , 17 ). However, it also had the following disadvantages: the single-ring ablation line was relatively long and it was difficult to isolate the PVs at the initial ablation attempt.…”
Section: Discussionmentioning
confidence: 99%
“…ectopic beats initiating PAF should also be taken into account, especially the left atrial posterior wall (LAPW) (5). Previous studies reported that single-ring isolation (SRI) for paroxysmal and persistent AF and long-term freedom from arrhythmia were comparable to other AF ablation techniques (6)(7)(8). In addition, the superior vena cava (SVC) has been shown as one of the most important sites of non-PV AF triggers, and SVC isolation (SVCI), in addition to PV isolation, reduces the recurrence of AF (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that SRI plays an important role in decreasing the ablation time 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…Single ring isolation (SRI) is carried out based on physiological principles to electrically isolate the posterior left atrium and pulmonary veins. This approach limits the amount of ablation in the posterior left atrium, shortens the ablation time and has the potential to reduce collateral damage to the oesophagus, preventing the formation of atrial oesophageal stula 19,20 . On the other hand, a prior study revealed that the recurrence of atrial brillation is common after SRI.…”
Section: Introductionmentioning
confidence: 99%